Sistem Informasi Repository Tugas Akhir (TA) Politeknik Aceh Selatan - Muharratul Mina Rizky; Sabrina Ulia Mouna; M. Arinal Ihsan (Jurnal Inotera, 2023)
A "final assignment repository" is a medium or place for storing final assignments and theses in the form of PDF files (Portable Document Format). At the end of each semester, students must receive a final assignment course for the D3 level. In each university, the final assignment system is often different, but most still use the manual method. When a student's thesis trial and final assignment are printed, it is used as a book as proof that they have completed the thesis or final assignment. For the collection of thesis books, students are required to collect them in the library; often, other students look for study references and assignments in the reading room. For that reason, the author's problem is trying to design a website-based final project repository application using the Laravel framework. This application was built to store student final assignments. In this case, students can easily save the final project file. In this application, the reading room admin plays the role of manager of the final assignment file if students who have submitted it validate that the student has collected it. Majoring students can use this application to access applications that can be used as learning tools or references for their final project. A computerized system is expected to provide convenience and produce applications as expected.